The Utility of Both Hard and Soft Power in Modern International Relations - Davit Tchotchua (Antis Publisher, 2024)
This essay's first section defines hard and soft power and how they work together to create soft power. Next, various instances of the two principles' application in the formulation of foreign policy are discussed in order to evaluate their efficacy. There are also instances of the application of smart power in this discussion. According to the article, soft power's durability and longevity make it a more effective and efficient notion in modern global politics. Hard power, however, is becoming less valuable as the world order shifts against it. In the modern international system, smart power tactics are just as significant as soft power tactics. Nye proposed the concept of hard power and soft power distinctions almost twenty years ago. He characterizes command or hard power as coercive power used through inducements or threats, and power as the